Disability Affects the 6-Minute Walking Distance in Obese Subjects (BMI>40 kg/m2) - Donini, Lorenzo Maria; Poggiogalle, Eleonora; Mosca, Veronica; Pinto, Alessandro; Brunani, Amelia; Capodaglio, Paolo (PloS one, 2013)
In obese subjects, the relative reduction of the skeletal muscle strength, the reduced cardio-pulmonary capacity and tolerance to effort, the higher metabolic costs and, therefore, the increased inefficiency of gait together with the increased prevalence of co-morbid conditions might interfere with walking. Performance tests, such as the six-minute walking test (6MWT), can unveil the limitations in cardio-respiratory and motor functions underlying the obesity-related disability. Therefore the aims of the present study were: to explore the determinants of the 6-minute walking distance (6MWD) and to investigate the predictors of interruption of the walk test in obese subjects. Obese patients [body mass index (BMI)>40 kg/m(2)] were recruited from January 2009 to December 2011. Anthropometry, body composition, specific questionnaire for Obesity-related Disabilities (TSD-OC test), fitness status and 6MWT data were evaluated. The correlation between the 6MWD and the potential independent variables (anthropometric parameters, body composition, muscle strength, flexibility and disability) were analysed. The variables which were singularly correlated with the response variable were included in a multivariated regression model. Finally, the correlation between nutritional and functional parameters and test interruption was investigated. 354 subjects (87 males, mean age 48.5 ± 14 years, 267 females, mean age 49.8 ± 15 years) were enrolled in the study. Age, weight, height, BMI, fat mass and fat free mass indexes, handgrip strength and disability were significantly correlated with the 6MWD and considered in the multivariate analysis. The determination coefficient of the regression analysis ranged from 0.21 to 0.47 for the different models. Body weight, BMI, waist circumference, TSD-OC test score and flexibility were found to be predictors of the 6MWT interruption. The present study demonstrated the impact of disability in obese subjects, together with age, anthropometric data, body composition and strength, on the 6-minute walking distance.